Implementasi Withholding Tax Pajak Penghasilan (PPH) Pasal 23 Di PT. Serasi Autoraya Pada Tahun 2020-2022 - Maryani Jurnal Pajak Vokasi (JU, Maryani; Prasetiyani, Erni (Jurnal Pajak Vokasi (JUPASI), 2023)
This study aims to investigate the implementation of the Withholding Tax System on Article 23 Income Tax (PPh) at PT Serasi Autoraya. This study analyzes how the system is implemented at PT Serasi Autoraya and identifies the obstacles or constraints faced by the company in implementing the tax deduction system. In addition, this research also ze the efforts made by the company to overcome these obstacles through training or training programs that aim to increase the understanding and knowledge of employees regarding this matter. The research method used is a qualitative approach with a descript ive research type. Data collection is done through interviews, observation, and documentation. This study refers to the theory of George C. Edwards III. The hope, research results this will provide useful insights for PT Serasi Autoraya in improving the im plementation of the PPh Article 23 tax deduction system. The research findings show that the implementation of withholding tax at PT Serasi Autoraya is in accordance with the provisions of the Tax Law. This abstract provides a brief description of the aims , methods, and findings of this study, which source of relevant and useful information for readers who can be a interested in this topic.